APPLICATION OF ELECTROSLAG CRUCIBLE MELTING FOR PRODUCTION OF CASTINGS OF IMPORTANT FUNCTION, USED IN MACHINE-BUILDING - V. A. Zemtsov; D. A. Meshkov; I. O. Sazonenko (Литьë и металлургия)
Use of electroslag crucible remelting with accumulation of  liquid metal allows to reduce considerably the requirements to accuracy of keeping up of electric parameters and in that way to provide possibility of use of  consumable electrodes.